Pemanfaatan Wayang Kertas dalam Pembelajaran Vaṭṭaka Jātaka untuk Meningkatkan Pemahaman Tentang Lobha di SMB Ariya Magga - Oka Sapda Renanda (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
This research is motivated by the importance of moral education in shaping the character of the younger generation, especially in Buddhist teachings that emphasize self-control over lobha (greed). The story of Vaṭṭaka Jātaka, which tells the story of a quail and a crow, is an effective means of teaching these values. However, the conventional learning methods used at the Ariya Magga Buddhist Sunday School (SMB) are considered less interesting and interactive, thus inhibiting students' in-depth understanding. Therefore, this study formulates the question: how to design backward design-based learning with paper puppet media to improve understanding of lobha, and what are the challenges and strategies for its implementation. This study uses a classroom research method based on backward design. The stages include identifying expected outcomes, determining assessment evidence, and designing learning experiences using paper puppets as the main media. The results of the study indicate that the use of paper puppets successfully increased student involvement actively, helped visualize the Vaṭṭaka Jātaka story, and facilitated understanding of the moral values ​​of lobha. The challenges that emerged included limited time and media availability, but they could be overcome through teacher-student collaboration and teacher creativity in utilizing traditional media. Thus, this study proves that the integration of creative media based on local culture with a backward design approach is an effective strategy in improving students' understanding of Buddhist moral values.